Lord of the flies - Golding, William, 1911-1993 (London Faber and Faber, 1958)
"William Golding's unforgettable classic of boyhood adventure and the savagery of humanity comes to Penguin Classics in a stunning Graphic Deluxe Edition with a new foreword by Lois Lowry As provocative today as when it was first published in 1954, Lord of the Flies continues to ignite passionate debate with its startling, brutal portrait of human nature. William Golding's compelling story about a group of very ordinary boys marooned on a coral island has been labeled a parable, an allegory, a myth, a morality tale, a parody, a political treatise, and even a vision of the apocalypse. But above all, it has earned its place as one of the indisputable classics of the twentieth century for readers of any age. This Penguin Classics Graphic Deluxe Edition features an array of special features to supplement the novel, including a foreword by Lois Lowry, an introduction by Stephen King, an essay by E. M. Forster, an essay on teaching and reading the novel and suggestions for further exploration by scholar Jennifer Buehler, and an extended note by E. L. Epstein, the publisher of the first American paperback edition of Lord of the Flies. For more than seventy years, Penguin has been the leading publisher of classic literature in the English-speaking world. With more than 1,700 titles, Penguin Classics represents a global bookshelf of the best works throughout history and across genres and disciplines. Readers trust the series to provide authoritative texts enhanced by introductions and notes by distinguished scholars and contemporary authors, as well as up-to-date translations by award-winning translators"--
Keywords: Survival -- Psychological aspects -- Fiction; Interpersonal relations in children -- Fiction; Regression (Psychology) -- Fiction; Shipwreck survival -- Fiction; Islands -- Fiction; Boys -- Fiction; FICTION / Classics; FICTION / Psychological; FICTION / Action & Adventure; Psychological fiction; Adventure fiction